2018
DOI: 10.1038/s41598-018-19352-8
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of foreign language in fear acquisition

Abstract: Emotions are at the core of human nature. There is evidence that emotional reactivity in foreign languages compared to native languages is reduced. We explore whether this emotional distance could modulate fear conditioning, an essential mechanism for the understanding and treatment of anxiety disorders. A group of participants was verbally informed (either in a foreign or in a native language) that two different stimuli could be either cueing the potential presence of a threat stimulus or its absence. We regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 34 publications
7
40
1
Order By: Relevance
“…Given that using a foreign language increases cognitive load due to the differences in the knowledge and use of foreign and native languages, we expected similar results for the foreign language as we observed with the brightness scale. In fact, preceding studies have demonstrated a partial emotional detachment of bilingual participants when presented with certain scenarios in their foreign language (see García-Palacios et al, 2018;Iacozza, Costa, & Duñabeitia, 2017). But, contrary to our initial intuition, evaluations were not affected by a foreign language effect, nor was the effect of scale modulated by language.…”
Section: Discussioncontrasting
confidence: 95%
“…Given that using a foreign language increases cognitive load due to the differences in the knowledge and use of foreign and native languages, we expected similar results for the foreign language as we observed with the brightness scale. In fact, preceding studies have demonstrated a partial emotional detachment of bilingual participants when presented with certain scenarios in their foreign language (see García-Palacios et al, 2018;Iacozza, Costa, & Duñabeitia, 2017). But, contrary to our initial intuition, evaluations were not affected by a foreign language effect, nor was the effect of scale modulated by language.…”
Section: Discussioncontrasting
confidence: 95%
“…In a more recent study using emotionally realistic sentence contexts, access to negative information in the second language of immersed, proficient Polish–English bilinguals appeared to be reduced (Jończyk et al., 2016). Furthermore, converging observations based on pupil dilation (Iacozza et al., 2017) and electrodermal measurements (Jankowiak and Korpal, 2017; see also García-Palacios et al., 2018) lend support to the idea that individuals are more detached from emotionally charged information in the L2 (for a discussion of affective disembodiment in bilingualism, see Pavlenko, 2012; Jończyk, 2016c; Sheikh and Titone, 2016), at the same time providing neurophysiological support for findings reported in introspective and clinical bilingual contexts (see Pavlenko, 2012; Caldwell-Harris, 2015; Jończyk, 2016a).…”
Section: Discussionmentioning
confidence: 63%
“…We employed the S1–S2 paradigm commonly implemented in studies of anticipation in combination with ERPs to investigate the relative amplitude of anticipatory potential variations elicited by stimulus cues (see Wu and Thierry, 2017, for a similar approach in the context of preparation for speaking). To our knowledge, only one study has previously investigated a possible interaction between affective anticipation and language of operation using physiological measures (García-Palacios et al., 2018). However, that study focused on language use (counting task), not semantic processing, and targeted physiological measures that are a proxy for stress levels in a fear conditioning context (pupil dilation and electrodermal activity).…”
Section: Introductionmentioning
confidence: 99%
“…In an L2 context, the non-dominant language can start to function like the dominant language to create optimal performance for bilinguals during conversations with different language contexts. García-Palacios et al (2018) and Iacozza et al (2017) observe that foreign languages are generally learned in emotionally neutral academic environments, while native languages are acquired in emotionally rich family contexts. They investigate if this difference in learning contexts influences emotional response on emotionally-charged sentences.…”
Section: Being Multilingualmentioning
confidence: 99%